THE TEACHER MORALS IN TEACHING ACCORDING TO K.H. HASYIM ASY’ARI IN THE BOOK OF ADABUL ‘ALIM WAL MUTA’ALLIM - Sari, Diana; Hidayat, Rahmat; Lubis, M. Fauzi (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2023)
This research is based on a phenomena of teachers in Indonesia who are still found to have no nable character, so that it does not reflect the morals of a good teacher. This research aims to determine: (1) The teacher’s character towards oneself according to K.H. Hasyim Asy’ari in the book of Adabul ‘Alim Wal Muta’allim, (2) The teacher’s character when teaching according to K.H. Hasyim Asy’ari the book of Adabul ‘Alim Wal Muta’allim, (3) The teacher’s characters towards students according to K.H. Hasyim Asy’ari the book of Adabul ‘Alim Wal Muta’allim, (4) The relevance of teacher morals to students according to K.H. Hasyim Asy’ari the book of Adabul ‘Alim Wal Muta’allim to current education at this time. This type of research is library research. Data collection uses documentation techniques and in data analysis uses content analysis techniques in obtaining the valid data.